Effects of Irradation on Holmium AcetylAcetonate Microspheres - Boekestijn, Imke (Student Undergraduate Research E-journal!, 2019)
The effects of irradiation on recently developed holmium acetylacetonate (HoAcAc) microspheres have been investigated by exposing HoAcAc microspheres to different irradiation conditions (types and doses) and temperatures. An accurate and detailed characterization of the chemical and physical properties of the HoAcAc microspheres before and after exposure to different conditions enabled the determination of the influence of neutron and/or gamma irradiation on the HoAcAc microspheres. The most important observation is that irradiation has a damaging effect on the microspheres, which occurs mostly at chemical level. Furthermore, results reveal a positive influence of the temperature in combination with irradiation on the microspheres.